(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Shekhovtsova S. A. Vocational and pedagogical training of university students in the context of subject-activity approach The article deals with the conceptual ideas of the subjective and performing approach to the students’ professional and pedagogical preparation and the crucial stages and difficulties of professional and pedagogical development of future teachers are determined.